TEACHERS' DEMAND FOR TRAINING AND PROFESSIONAL IMPROVEMENT IN THE FIELD OF E-LEARNING TECHNOLOGY - SALATA, Elzbieta (Trends in education, 2014)
Knowledge and skills of acquiring it in a fast and effective way play the crucial role in the society of 21st century. Employees' improvement is regarded as the key factor of growth in labour effectiveness. In this case traditional trainings become no longer sufficient as information technology is what gains importance in the process of acquiring knowledge and education. Apart from education, distant learning or e-learning is currently used in almost every field of social life. Educational progress poses a lot of challenges to a teacher. To meet them they can choose to participate in different forms of training and further education with the use of e-learning technology. The paper aims to diagnose teachers' needs in the field of education involving e-learning technology.
Keywords: teacher; training; perfecting; e-learning.